2019
DOI: 10.1088/1742-6596/1423/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Data comparison of the effects of feeding ginkgo leaf fermentation and Chinese herbal medicine on meat ducks

Abstract: In order to study the effect of feeding Ginkgo leaf fermentation and Chinese herbal medicine on meat duck, we added Ginkgo leaf fermentation and Chinese herbal medicine additive to the daily feed of meat ducks, and set up a control group (basic feed), a western medicine group (basic feed+150mg/kg aureomycin), an experimental group 1 (basic feed + Chinese herbal medicine 0.1%) and an experimental group 2 (basic feed + 0.1% Chinese herbal medicine + 2.5% Ginkgo leaf ferment). We fed the ducks for 45 days, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In the liver, ALP is cytoplasmic and present in the tubular membranes of stem cells, and more than 80% of serum ALP is released from the liver and bone (38). Serum ALP is a marker of liver damage reflecting diseases of the hepatobiliary system and has been widely used as a predictive tool for cholestatic liver disease (39,40). LDH is widely distributed in eggs, liver, heart, kidneys and muscles, and is a cytoplasmic oxidoreductase enzyme that indicates damage and oxidative stress in the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the liver, ALP is cytoplasmic and present in the tubular membranes of stem cells, and more than 80% of serum ALP is released from the liver and bone (38). Serum ALP is a marker of liver damage reflecting diseases of the hepatobiliary system and has been widely used as a predictive tool for cholestatic liver disease (39,40). LDH is widely distributed in eggs, liver, heart, kidneys and muscles, and is a cytoplasmic oxidoreductase enzyme that indicates damage and oxidative stress in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Yeh et al (43) demonstrated that B. subtilis variant N21+, B. coagulans variant L12 in FF led to decreased activity of serum LDH in broilers, which could be caused by the decomposition of the fermentation substrate, or by the reduction of antinutrients due to heat treatment during the pelleting process, thus reducing the activity of serum LDH. Additionally, Wang et al(40) found that the addition of ginkgo FF to the diet results in a significant decrease in serum ALP activity in meat ducks. In this study, the ALP activity of all FF groups decreased significantly, and the 5.0 and 7.5% FF groups significantly decreased…”
mentioning
confidence: 99%
“…Although there have been considerable researches on ginkgo biloba, relatively little research was conducted on ginkgo kernels. Various ginkgo products such as ginkgo tea, ginkgo wine, and ginkgo beverages are readily available in the market, but limited research has been conducted related to lactic acid bacteria (LAB) fermented ginkgo kernel juice drinks [6] . To address this issue, numerous efforts have been made to improve the fermentation of ginkgo kernel juice, reduce its toxicity, and explore its development and application.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies on ginkgo mainly focuses on ginkgo leaves, while there are relatively few studies on ginkgo kernels. Ginkgo products mainly include canned ginkgo kernel, ginkgo wine, and beverages ( 10 , 11 ). However, only a few studies had been conducted on fermented silver almonds.…”
Section: Introductionmentioning
confidence: 99%